2018
DOI: 10.7710/2162-3309.2226
|View full text |Cite
|
Sign up to set email alerts
|

How are we Measuring Up? Evaluating Research Data Services in Academic Libraries

Abstract: INTRODUCTIONIn the years since the emergence of federal funding agency data management and sharing requirements (http://datasharing.sparcopen.org/data), research data services (RDS) have expanded to dozens of academic libraries in the United States. As these services have matured, service providers have begun to assess them. Given a lack of practical guidance in the literature, we seek to begin the discussion with several case studies and an exploration of four approaches suitable to assessing these emerging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…A similar model was developed at the University of Michigan, with all library liaison roles rewritten to include research data services, along with a core team of librarians with deeper expertise focused on curation, data management, and sharing (Coates et al, 2018). In this model, a working group was charged with providing professional development to all library staff ("in-reach to librarians") to establish a base understanding of research data services, with specific handoff strategies for more specific or advanced questions (Martin & Oehrli, 2015;Coates et al, 2018). Liaisons were assessed to determine if they "felt they were able to provide the services themselves ("do"), provide the service working alongside someone else ("collaborate"), or want to refer a service request to someone else ("refer")" (Coates et al, 2018, 13).…”
Section: University Of Michigan: a Hierarchical Style With Triage Bamentioning
confidence: 99%
“…A similar model was developed at the University of Michigan, with all library liaison roles rewritten to include research data services, along with a core team of librarians with deeper expertise focused on curation, data management, and sharing (Coates et al, 2018). In this model, a working group was charged with providing professional development to all library staff ("in-reach to librarians") to establish a base understanding of research data services, with specific handoff strategies for more specific or advanced questions (Martin & Oehrli, 2015;Coates et al, 2018). Liaisons were assessed to determine if they "felt they were able to provide the services themselves ("do"), provide the service working alongside someone else ("collaborate"), or want to refer a service request to someone else ("refer")" (Coates et al, 2018, 13).…”
Section: University Of Michigan: a Hierarchical Style With Triage Bamentioning
confidence: 99%
“…The past decade has witnessed growth in the provision of data services by academic health sciences libraries, with new service models including training in research data management, data analysis, and coding for data science in languages like Python and R [1][2][3][4][5][6][7][8][9][10]. In our academic health sciences library, we began offering data services in the form of research data management workshops in 2012.…”
mentioning
confidence: 99%
“…After each workshop, we conducted attitudinal surveys of participant experience. We also instituted regular biannual retreats for library faculty and staff to engage in reflective practice [1], but we had not initially done longer-term follow-up with workshop participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results help librarians build a foundation for future DMP services [2]. Coates and others examined five case studies that highlight common challenges for librarians to evaluate existing research data services in academic libraries, and suggested that evidence-based approach provides valuable information for assessing the still-emerging services [3]. Goben and Griffin's study confirmed, "Researchers are most worried about storage, sharing, and issues that revolve around longer term access to data…" Therefore, there are needs for "thoughtfully planned academic RDS [Research Data Service] that are simultaneously broad in scope and strategically focused on addressing specific local needs" [4].…”
Section: Selected Literature Reviewmentioning
confidence: 99%